CHALLENGES AND OPPORTUNITIES OF DIGITAL AGRICULTURE IN PROMOTING SUSTAINABILITY AND SOCIAL INCLUSION AMONG SMALL-SCALE FARMERS IN BRAZIL - da Cruz Neto, Geraldo Antônio; Merida, Carolina; Lacerda, Murilo Couto; Guimarães, Rejaine Silva; Costa, Patrícia Spagnolo Parise; Machado, Línia Dayana Lopes (Editora Impacto Científico, 2025)
The article analyzes how digital agriculture, or smart agriculture, can simultaneously enhance environmental sustainability and promote social inclusion among small rural producers in Brazil. It argues that technologies such as sensors, IoT, big data and cloud computing make it possible to optimize input use, reduce waste, monitor climate conditions and increase productivity with lower environmental impact. However, it shows that these benefits are unevenly distributed due to low connectivity in rural areas, the high cost of equipment and regional asymmetries in income and infrastructure. Data from the 2017 Agricultural Census indicate that more than 70% of farms did not have internet access, which limits the use of management applications, marketing platforms and remote technical assistance. This scenario is compounded by low levels of schooling and digital literacy among most producers, which hinders the appropriation of these technologies. The article also examines the Climate-Smart Agriculture (CSA) agenda, highlighting its potential to integrate productivity, climate adaptation and emissions mitigation, while warning of the risk of excluding small producers when policies and programs privilege large enterprises. It concludes that digital agriculture will only become an effective driver of sustainability and inclusion if it is articulated with robust policies for connectivity, training, rural extension and social participation, guided by socio-environmental justice. DOI: https://doi.org/10.56238/edimpacto2025.080-007